2001
DOI: 10.1159/000051782
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Irritative Effect of Methylrosaniline Chloride (Gentian Violet)

Abstract: Background: There are no published studies of the effect of methylrosaniline chloride (MRC) on inflammation when used at the concentration recommended in the New German Formulary. A tissue-damaging effect has been described in animal studies and at higher concentrations in humans. Objective: To determine whether 0.5% MRC increases or reduces skin damage in irritative dermatitis. Methods: The study was carried out on the sodium lauryl sulfate (SLS) skin irritation model in 18 healthy volunteers. The impact of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…In ookinete transformation, MMV665941 showed the third best inhibition rate. This compound, which is also called methylrosaniline, has a dermatological topical use, (27) and may target a steroldependent function. Plasmodium parasites require sterol lipids, which they can scavenge from the host.…”
Section: Discussionmentioning
confidence: 99%
“…In ookinete transformation, MMV665941 showed the third best inhibition rate. This compound, which is also called methylrosaniline, has a dermatological topical use, (27) and may target a steroldependent function. Plasmodium parasites require sterol lipids, which they can scavenge from the host.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been reported that cutaneous/mucous membrane disorders caused by methylrosanilinium chloride are mainly due to a primary concentration-dependent irritant effect, while a lower concentration does not affect epithelial regeneration. [15][16][17] Due to its potent antibacterial activity against MRSA, methylrosanilinium chloride has increasingly being used for the treatment of prosthetic graft infection 11,12) and decubitus ulcer 13) over the past several years. However, liquid preparations of methylrosanilinium chloride were used in previous studies and a method of percutaneous site disinfection for VAD patients has not been established.…”
Section: Discussionmentioning
confidence: 99%
“…Gloor et al noted anti-irritative effect of 0.5% gentian violet. 22 They found that 0.5% gentian violet reduces skin damage in irritative dermatitis. It also provides immediate pain relief in acute painful eczematous lesions.…”
Section: Dermatitismentioning
confidence: 99%